Analysis of Energy Harvesting Systems from RF to Dc Power - Muhammad Fitra Zambak; Ar Ridho; Rohana Rohana; Suwarno4 Suwarno (Faculty of Engineering, Malikussaleh University, 2024)
Abstract Harvesting energy system from RF signals has great potential as an alternative energy source. This research focuses on the performance of an energy harvesting system that converts RF signals into DC Power using components such as Schottky BAT-17 diodes and MKM 100V 1nF capacitors. The main components used in this matching network are a 100 Ohm resistor, 100nH inductor, and 0.33pF capacitor. The 100 Ohm resistor was selected based on impedance analysis to achieve good matching, reduce signal reflections, and increase power transfer efficiency. A 100nH inductor is used to match impedance and filter out unwanted frequencies, chosen because this value provides appropriate inductance at the target frequency. Tests were carried out at distances of 1m, 3m and 5m with Vpp results of 30.4 mV at distances of 1m and 3m, and 45.6 mV at a distance of 5m. The obtained voltage decreases with increasing distance: 3.35 V at 1m, 3.19 V at 3m, and 2.85 V at 5m. Energy conversion efficiency also decreases with increasing distance. In the long term, performance shows good stability even though there is a decrease in voltage and efficiency. Technical obstacles such as signal degradation and efficiency can be overcome by network matching optimization.